Fabrication and characterization of flame retardant 4 and polydimethylsiloxane as substrates for a label-free DNA sensor / Irni Hamiza Hamzah, Emilia Noorsal, Mohammad Nizam Ibrahim, Asrulnizam Abd Manaf and Othman Sidek - Noorsal, Emilia; Ibrahim, Mohammad Nizam; Abd Manaf, Asrulnizam (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
Silicon, glass, and ceramic are commonly used base substrates for gold (Au) deposition on label-free DNA biosensors. This study aimed to investigate the suitability of applying flame retardant 4 (FR4) as a base substrate and polydimethylsiloxane (PDMS) as a coating substrate. A thermal evaporator was used to fabricate copper/nickel/Au metals and ensure even deposition of Au throughout FR4. UV exposure soft lithography and wet etching were applied to develop a three-electrode pattern on the metals fabricated on FR4. A simple and straightforward technique on PDMS–FR4 bonding was proved to work at the shear strength of 55 kPa. A cyclic voltammetry (CV) method was performed using the fabricated FR4 sensor to analyze bare Au, DNA immobilization and hybridization. The FR4-based Au fabricated with PDMS acted as a coating layer between terminals and sensing electrodes, and can thus be used as a label-free DNA sensor.